2011
DOI: 10.1111/j.1472-8206.2011.00967.x
|View full text |Cite
|
Sign up to set email alerts
|

Management of the airway without the use of neuromuscular blocking agents: the use of remifentanil

Abstract: Remifentanil belongs to opioid drugs, and its pharmacokinetic characteristics make it unique in this class of drugs and appropriate for use during intubation without neuromuscular blockage. This up-to-date review aims to summarize the findings of recent studies regarding remifentanil and intubation. Remifentanil combined either with propofol or with inhaled anesthetic agents has been proved to provide acceptable intubating conditions. Regarding children patients, remifentanil can be used safely, and as far as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
7
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 88 publications
2
7
0
Order By: Relevance
“…Our results are largely consistent with those of a previous narrative review, which included adult and paediatric patients; however, we undertook a systematic search, risk of bias and quality assessment of studies [16].…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Our results are largely consistent with those of a previous narrative review, which included adult and paediatric patients; however, we undertook a systematic search, risk of bias and quality assessment of studies [16].…”
Section: Discussionsupporting
confidence: 85%
“…Previous reviews on this topic were published over 10 years ago [15,16] and further studies have been completed since. In light of this, the objective of this systematic review and meta-analysis was to determine the efficacy and safety of remifentanil for providing comparable conditions for tracheal intubation compared with NMB drugs in adult patients.…”
Section: Introductionmentioning
confidence: 99%
“…Intubation without a muscle relaxant is achievable with deep anesthesia or with the combination of propofol and remifentanil. 2427 However, difficult intubations and adverse hemodynamic events are more frequently related to intubation without muscle relaxants, 25,26 and excellent intubation conditions are more frequent when muscle relaxation is used. 24 …”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported the incidence of hypotension and bradycardia after remifentanil use, which may explain our results. [22,23] In addition, there were 3 patients in group 2.0 who had closed vocal cords during the induction period. This seems to be related to the muscle rigidity following a high dose of remifentanil.…”
Section: Discussionmentioning
confidence: 99%